The anti-bacterial effect of phenolic compounds from three species of marine macroalgae - ALIFAH EVI SCANIA; Abdul Razaq Chasani (Society for Indonesian Biodiversity, 2021)
Abstract. Scania AE, Chasani AR. 2021. The anti-bacterial effect of phenolic compounds from three species of marine macroalgae. Biodiversitas 22: 3412-3417. Bacterial infection is still a serious problem in human health due to many bacteria that are resistant to synthetic antibiotics. Natural antibiotics are needed for substituting synthetic antibiotics such as antibiotics derived from marine macroalgae. Marine macroalgae respond to extreme environmental conditions by producing secondary metabolites containing bioactive substances. Bioactive substances such as phenolic compounds in marine macroalgae may have an antibacterial effect on bacteria. Our research was aimed to detect the presence of phenolic compounds in three species of marine macroalgae (Ulva lactuca (Chlorophyta), Sargassum polycystum (Phaeophyta), Palmaria palmata (Rhodophyta)), and also to determine the most effective inhibition of phenols-contained extracts of marine macroalgae to the growth of Escherichia coli and Salmonella typhi. Our research was conducted through field sampling for collecting samples and laboratory work for identifying and extracting samples including qualitative testing of phenolic compounds, rejuvenating bacteria, preparing the tested bacteria, and determine the inhibition index of extracts against E.coli and S.typhi. Our results indicated that the extract of U. lactuca, S. polycystum, and P.palmata contained phenolic compounds. Phenols-contained extract of Sargassum polycystum is the most effective in inhibiting the growth of E. coli and S. typhi. The incubation temperature, the type of bacteria influence the antibacterial activity of marine macroalgae.